2020
DOI: 10.3390/nu12103077
|View full text |Cite
|
Sign up to set email alerts
|

Mikania micrantha Extract Inhibits HMG-CoA Reductase and ACAT2 and Ameliorates Hypercholesterolemia and Lipid Peroxidation in High Cholesterol-Fed Rats

Abstract: The present study aimed to determine the effect of an ethyl acetate extract of Mikania micrantha stems (EAMMS) in hypercholesterolemia-induced rats. Rats were divided into a normal group (NC) and hypercholesterolemia induced groups: hypercholesterolemia control group (PC), simvastatin group (SV) (10 mg/kg) and EAMMS extract groups at different dosages of 50, 100 and 200 mg/kg, respectively. Blood serum and tissues were collected for haematological, biochemical, histopathological, and enzyme analysis. Total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As shown in Figure 6, DCQA series and multiple polyphenolic contents, such as kaempferol, rhamnetin, isorhamnetin, and quercetin, were identified in the AGEM70M fraction. In multiple studies, plant polyphenols were shown to be effective in lowering cholesterol and lipid levels by modulating HMGR and FAS activities [30][31][32][33]. Thus, not only the active DCQA contents in AGEM70 but also the polyphenols may have been responsible for the dual-modal activity.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 6, DCQA series and multiple polyphenolic contents, such as kaempferol, rhamnetin, isorhamnetin, and quercetin, were identified in the AGEM70M fraction. In multiple studies, plant polyphenols were shown to be effective in lowering cholesterol and lipid levels by modulating HMGR and FAS activities [30][31][32][33]. Thus, not only the active DCQA contents in AGEM70 but also the polyphenols may have been responsible for the dual-modal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia refers to a condition of an increase in total cholesterol level, LDL, or triglyceride, and a decrease in HDL level, which is defined as a lipid metabolism disorder (Ibrahim et al, 2020;Wells et al, 2015). Hypercholesterolemia is indicated by an increase in cholesterol level ≥240 mg/dL (Bunton et al, 2011;He et al, 2004;Koo et al, 2021;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This will lead to hypercholesterolemia or increased blood. [2][3][4] Hypercholesterolemia is suspected to be a factor in the development of coronary heart disease. 1,3,5 Furthermore, high LDL (low-density lipoprotein) cholesterol levels in patients can accelerate the occurrence of plaque which causes narrowing and hardening of the arteries.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5 Furthermore, high LDL (low-density lipoprotein) cholesterol levels in patients can accelerate the occurrence of plaque which causes narrowing and hardening of the arteries. 3,4,[6][7][8] Atherosclerosis is a chronic condition characterized by the buildup of plaque in the arteries, which causes narrowing, hardness, and even total blockage. 6,8,9 Furthermore, it causes blood circulation to become not smooth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation